Usborne Greek myths for young children - Amery, Heather; Edwards, Linda, 1948- (London : Usborne ; Tulsa, Okla : EDC Pub., 2001)
A collection of illustrated Greek myths, adapted for young readers. Includes a list of Greek names, with pronunciations.
3.1
K-3
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Greek; Greek mythology